The mediated erotic lover. The role of pornography in the negotiation of gender roles and desire amongst Italian heterosexual couples. Issue 4 (18th May 2020) - Scarcelli, Cosimo Marco; Stella, Renato
ABSTRACT: Considering gender, sexuality and sexual desire are culturally and socially constructed through social learning and interaction and pornography as a cultural practice, this article focuses on how the discourse that young Italian heterosexual couples construct around pornography can illustrate their definition and negotiation of desire, and gender roles. The work is based on 50 e-mail interviews with 21 female and 29 male young Italians aged between 20 and 24 years old. Our interviewees (both male and female) express the idea of heterosexual male desire as implacable, natural and a fundamental expression of masculinity. In the complex plot delineating desire, gender roles and heterosexual scripts in heterosexual couples, we suggest that pornography might be seen as an erotic lover capable of embodying practices and desires that cannot be expressed or shared by the couple.